2018
DOI: 10.1038/nature25967
|View full text |Cite
|
Sign up to set email alerts
|

Humans thrived in South Africa through the Toba eruption about 74,000 years ago

Abstract: Approximately 74 thousand years ago (ka), the Toba caldera erupted in Sumatra. Since the magnitude of this eruption was first established, its effects on climate, environment and humans have been debated. Here we describe the discovery of microscopic glass shards characteristic of the Youngest Toba Tuff-ashfall from the Toba eruption-in two archaeological sites on the south coast of South Africa, a region in which there is evidence for early human behavioural complexity. An independently derived dating model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 46 publications
1
86
0
Order By: Relevance
“…Marine occurrences prefixed "SO" are from the Sonne-93 cruise (Weber et al, 2003). Map excludes YTT occurrences from Lake Malawi, East Africa (Lane et al, 2013) and on the southern coast of South Africa (Smith et al, 2018). For locality information, see Supplementary Table 2 [Color figure can be viewed at wileyonlinelibrary.com] compositions, biotite compositions or spontaneous fission track density (Smith et al, 2011;Westgate et al, 2013Westgate et al, , 2014Pearce et al, 2014b;Westgate and Pearce, 2017).…”
Section: Samples and Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marine occurrences prefixed "SO" are from the Sonne-93 cruise (Weber et al, 2003). Map excludes YTT occurrences from Lake Malawi, East Africa (Lane et al, 2013) and on the southern coast of South Africa (Smith et al, 2018). For locality information, see Supplementary Table 2 [Color figure can be viewed at wileyonlinelibrary.com] compositions, biotite compositions or spontaneous fission track density (Smith et al, 2011;Westgate et al, 2013Westgate et al, , 2014Pearce et al, 2014b;Westgate and Pearce, 2017).…”
Section: Samples and Analytical Methodsmentioning
confidence: 99%
“…Marine occurrences prefixed “SO” are from the Sonne‐93 cruise (Weber et al , ). Map excludes YTT occurrences from Lake Malawi, East Africa (Lane et al , ) and on the southern coast of South Africa (Smith et al , ). For locality information, see Supplementary Table 2 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Introductionmentioning
confidence: 99%
“…Within the last two decades, tephrochronology has become more common in archaeological research due to advancements in extraction and identification methods (Blockley et al ., ) and due to its ability to work as a correlative tool as well as to more accurately date deposits (Riede and Thastrup, ; Douka et al ., ; Lowe et al ., ; Smith et al ., ). While the basic approach is similar to correlative studies that have been conducted as far back as the early 1950s (Lowe, ), the use of cryptotephra (microscopic volcanic glass shards) in archaeological research has shown great success for large‐scale correlations (Lowe et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…peat bogs, marine and lake sediments, ice cores) and can travel as far as 9000 km from the source eruption (Smith et al ., ), allowing for isochrons (precise temporal markers) to be established between archaeological and paleoenvironmental records across vast regions (Lane et al ., ; Lowe et al ., ). However, the ability to find, recognize and analyze cryptotephra involves specialized extraction methods that target the non‐visible shards (Blockley et al ., ; Lane et al ., ), making it possible to locate these microscopic shards even at very low quantities (Smith et al ., ). The extraction of shards from host sediments can be very difficult and even when shards are identified, using them as stratigraphic markers can be problematic.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature (Yost et al, ), the maximum simulated global mean cooling anomalies range from severe 18 °C to a relatively mild 3.5 °C, which is only 5 times larger than the recent cooling observed after the 1991 Pinatubo eruption (Stenchikov et al, ). Paleodata even suggest that the climate of East Africa was not substantially affected at all (Lane et al, ; Oppenheimer, ; Smith et al, ; Yost et al, ). Thus, the assumption itself regarding extreme cooling after the Toba eruption may not be valid.…”
Section: Introductionmentioning
confidence: 99%